Testing the Identification/Production Hypothesis of Implicit Memory in Schizophrenia: The Role of Response Competition. (22nd December 2015) - Marques, Valéria R.S.; Spataro, Pietro; Cestari, Vincenzo; Sciarretta, Antonio; Rossi-Arnaud, Clelia
Abstract: Objectives: Previous evidence indicates that patients with schizophrenia exhibit reduced repetition priming in production tasks (in which each response cue engenders a competition between alternative responses), but not in identification tasks (in which each response cue allows a unique response). However, cross-task comparisons may lead to inappropriate conclusions, because implicit tests vary on several dimensions in addition to the critical dimension of response competition. The present study sought to isolate the role of response competition, by varying the number of solutions in the context of the same implicit tasks.Methods: Two experiments investigated the performance of patients with schizophrenia and healthy controls in the high-competition and low-competition versions of word-stem completion (Exp.1) and verb generation (Exp.2).Results: Response competition affected both the proportions of stems completed (higher to few-solution than to many-solution stems) and the reaction times of verb generation (slower to nouns having no dominant verb associates than to nouns having one dominant verb associate). Patients with schizophrenia showed significant (non-zero) priming in both experiments: crucially, the magnitude of this facilitation was equivalent to that observed in healthy controls and was not reduced in the high-competition versions of the two tasks.Conclusions: These findings suggest that implicit memory is spared in schizophrenia, irrespective of the degree of response competition during the retrieval phase; in addition, they add to the ongoing debate regarding the validity of the identification/production hypothesis of repetition priming. ( JINS, 2015, 21, 314–321)